Increasing the Added Value of Wood Powder Waste into Biobriquettes as Renewable Energy Fuel in Nagari Sungai Buluh, Padang Pariaman Regency - Riski Gunawan Nasution; Raihan Aprila; Ririn Arsy Gunawan; Nurfajriana Husna Rahimi; Muhammad Rifan Ridha (Faculty of Engineering UNHAS, 2025)
This community service program aimed to address the problem of wood dust waste in Sungai Buluh Nagari, Padang Pariaman Regency, by converting it into biobriquettes as a renewable energy source. The wood dust waste generated by local woodcrafters has not been utilized optimally and is often burned directly, causing air pollution. Through a participatory approach, this program involved technical training, technology transfer, and hands-on mentoring in biobriquette production. Quantitative analysis through pre-test and post-test of 20 participants showed a significant increase in understanding, with the